2011
DOI: 10.1093/eurjhf/hfr139
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training in recently hospitalized heart failure patients enrolled in a disease management programme: design of the EJECTION-HF randomized controlled trial

Abstract: AimsThe Exercise Joins Education: Combined Therapy to Improve Outcomes in Newly-discharged Heart Failure (EJEC-TION-HF) study will evaluate the impact of a supervised exercise training programme (ETP) on clinical outcomes in recently hospitalized heart failure patients attending a disease management programme (DMP). MethodsThis multisite, pragmatic randomized controlled trial enrols patients discharged from participating hospitals with clinical evidence of heart failure who are willing and able to participate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…We have incorporated several novel features into our study design to meet the specific needs of older, frail recently hospitalized HF patients that distinguishes REHAB-HF from prior 29, 30 and ongoing 5658 investigations of exercise training in HF. During our pilot study, we observed unexpectedly severe impairments in all functional domains, including balance and mobility.…”
Section: Discussionmentioning
confidence: 99%
“…We have incorporated several novel features into our study design to meet the specific needs of older, frail recently hospitalized HF patients that distinguishes REHAB-HF from prior 29, 30 and ongoing 5658 investigations of exercise training in HF. During our pilot study, we observed unexpectedly severe impairments in all functional domains, including balance and mobility.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were defined as having CHF if they had documented evidence of: 1) symptoms including dyspnea, fatigue, and/or peripheral edema; 2) physical signs of heart failure at the time of hospital admission, including increased jugular venous pressure, a displaced apex beat, the presence of a third heart sound, and/or crepitation on chest auscultation; or 3) significant radiographic and/or echocardiographic findings suggesting heart failure. 8) Patients were excluded from this study for the following reasons: terminal illness, severe cognitive dysfunction, and psychological or physical disabilities. Patients who were waiting for coronary revascularization, insertion of an implantable cardioverter defibrillator, or cardiac resynchronization therapy, were also excluded.…”
Section: Methodsmentioning
confidence: 99%
“…[86] The effect of exercise training on survival in HFPEF is unknown, but will be examined in the Ejection-HF trial. [87]…”
Section: Treatment Of Hfpefmentioning
confidence: 99%